From Lyric to Prose - and Back Again. Kundera's Poetics in a Tension of Metaphoric and Metonymic Motivation - Češka, Jakub (Bohemica Olomucensia, 2016)
The study is focused on the relationship of lyric and epic in Milan Kundera's work. Milan Kundera differs resolutely from lyric in the novel Life Is Elsewhere. Nevertheless, the lyric is present at his writing till his late work. In the novel Identity, Milan Kundera paraphrases two poems from his collection Monologues. We could point out how much the lyric in the late work is an integral part of the novelist's gesture.
Keywords: Milan Kundera; Lyric; Metaphor; Metonymy; Identity; Monologues